Learning Strategy of the Kitab Washoya Al-Abaa’ Lil Abnaa’ in Forming Students’ Morals - Fitri, Novida Aprilina Nisa; Latifah, Kumala Azizatul (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
The origin of this research stemmed from the researcher's observation of students from early childhood to adulthood who still lacked morality towards others, particularly their parents. This study employs a case study research design and a qualitative methodology. The data sources used are primary and secondary sources. In collecting data, the researcher used interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and verification. In order to verify the validity of the data, the researcher employed triangulation techniques, gathered information from multiple sources, and utilized reference materials. The study's results show that students at TPQ (Taman Pendidikan Qur'an) Al-Barokah Pule Macanan implement the book Washoya Al-Abaa 'Lil Abnaa' in their moral formation by preparing materials and creating lesson summaries. Students at TPQ (Taman Pendidikan Quran) Al-Barokah Pule Macanan learn the Kitab Washoya Al-Abaa’ Lil Abnaa’ in three weekly meetings, namely every Saturday, Sunday, and Monday. Learning activities consist of introduction, content, and closing. Supporting and inhibiting factors for learning the Kitab Washoya Al-Abaa’ Lil Abnaa’ in the formation of morals of students at TPQ (Taman Pendidikan Quran) Al-Barokah Pule Macanan are changes. We observe the changes in two areas: moral knowledge and student behavior.